1993
DOI: 10.1159/000187291
|View full text |Cite
|
Sign up to set email alerts
|

Primary Glomeruionephritis with Predominant Mesangial Immunoglobulin G Deposits -A Distinct Entity?

Abstract: Six cases of primary glomeruionephritis with predominant IgG deposits in the mesangium are described on the basis of a review of renal-biopsy-proven 1,116 cases with primary glomeruionephritis between 1977 and 1990. All patients were female (6-52 years old). Six patients appeared with microscopic hematuria: 3 with episodes of gross hematuria and 3 with mild proteinuria, but none with the nephrotic syndrome. Renal function was normal except for 1 case (52 years old) complicated with hypertension. Serum levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
3
2

Year Published

1996
1996
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 10 publications
(11 reference statements)
2
11
3
2
Order By: Relevance
“…The mice were habituated for 1 week and then used for experiments. Induction of an accelerated model of IgA nephropathy was performed using the method reported by Sato et al 3,5) The right abdominal region was opened under ether anesthesia, and the right renal artery was ligated using suture thread to occlude the right kidney. After one week, colloidal carbon (Pilot Co., Tokyo, Japan) suspended in a 1% gelatin solution to block the reticuloendothelial system was administered intravenously to the mouse caudal vein at a dosage of 4 mg/100 g body weight.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mice were habituated for 1 week and then used for experiments. Induction of an accelerated model of IgA nephropathy was performed using the method reported by Sato et al 3,5) The right abdominal region was opened under ether anesthesia, and the right renal artery was ligated using suture thread to occlude the right kidney. After one week, colloidal carbon (Pilot Co., Tokyo, Japan) suspended in a 1% gelatin solution to block the reticuloendothelial system was administered intravenously to the mouse caudal vein at a dosage of 4 mg/100 g body weight.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, unilateral nephrectomy, blockade of the reticuloendothelial system, and oral sensitization in ddY mice have demonstrated that the deposition of IgA and pathological changes in glomeruli may be induced earlier than those in spontaneous ddY mice. [3][4][5] Transforming growth factor-b1 (TGF-b1) induces matrix synthesis in renal tissues, leading to the progression of IgA nephropathy. 6,7) When added to cultured human mesangial cells, aggregated IgA1 from patients with IgA nephropathy induces increases in TGF-b1 gene expression and secretion of extracellular matrix in cultured mesangial cells.…”
mentioning
confidence: 99%
“…На основе обзора 1116 почечных биопсий при пер-вичном ГН, проведённых в период между 1977 и 1990 гг., появились публикации Sato и соавт. [14], позже -Yoshikawa и соавт. [15].…”
Section: казанский медицинский журнал 2017 г том 98 №5unclassified
“…[14] 6 случаев IgG-нефрита, все больные были женского пола, с гематурией у всех и ПУ у 3 женщин, СКФ была в пределах нормы. Морфологически у всех была выявлена фокально-сегментарная альтерация, а при иммунофлюоресцентном методе у 4 -отло-жения фракции комплемента С3, у 1 -С1q.…”
Section: обзорыunclassified
“…Although there are several reports on glomerulonephritis associated with mesangial IgM deposits (IgM nephropathy) [3,4], there are only three reports about glomerulonephritis associated with mesangial IgG deposits in Japan. Sato et al [5] have reported that 6 of 1,116 patients with primary glomerulonephritis had IgG nephropathy. All 6 cases had microscopic hematuria with slightproteinuria, and PAS-positive nodular deposits in the mesangium, similar to IgA nephropathy, were observed in 2 of these 6 cases.…”
mentioning
confidence: 99%